STUDY OF OCCUPATIONAL SAFETY AND HEALTH ON BLASTING PROCESS IN ANDESITE STONE MINING AREA WITH HIRAC METHOD IN CV. ARTHA AGUNG BERSAMA, HULU GURUNG SUB-DISTRICT, KAPUAS HULU REGENCY - Prasetio, Abraham; Sutrisno, Hendri; Mukhtar, Wahdania; Meilasari, Fitriana; Syahrudin, Syahrudin (Fakultas Teknik Universitas Tanjungpura, 2023)
CV. Artha Agung Bersama is an andesite mining company that uses a blasting system. This mining activity can harm workers if they do not apply good K3 management in blasting activities. One of the hazards of blasting activity is flying rock. For this reason, it is necessary to identify potential hazards, assess the level of accident risk, and recommend risk control efforts. The method in this study is the HIRAC (hazard identification risk assessment and control) method. This activity has five potential hazards: broken drum straps, worker negligence, explosive sounds, fly rock, and workers walking in a hurry in locations with a lot of gravel. There are five risks of accidents from potential hazards: being hit by a drum, scratched hands, pinched fingers forming a critical cover, slipping, exposure to diesel fuel, hearing loss, and being hit by a rock. Of the five hazard risks, three risks are included in the priority one category, namely: scratched hands, pinched fingers forming key covers, slipping, exposure to diesel fuel, and being hit by rocks. One risk is included in priority category three: being hit by a drum. One risk category is very high, namely being hit by a rock. The recommended risk control hierarchy for blasting activities is engineering control, administration, and personal protective equipment.